Turkish Validity and Reliability of Short Form McGill Pain Questionnaire-2 in Patients with Chronic Cervical Radicular Pain Due to Disc Herniation - Ezgi Can,; Rumeysa Çetinkaya Bulutoğlu,; Hande Ece Öz,; Furkan Çetin,; Alp Eren Çelenlioğlu,; Ender Sir, (Archives of Rheumatology, 2025)
Background/Aims: This study aimed to evaluate the reliability and validity of the Turkish edition of the Short-Form McGill Pain Questionnaire-2 (SF-MPQ-2) among chronic cervical radicular pain (CRRP) cases caused by disc herniation. The secondary aim was to assess the relationship between TR-SFMPQ-2 and other pain and disability scales. Materials and Methods: Data from 103 CRRP patients at the Algology outpatient clinic were analyzed. In addition to TR-SF-MPQ-2, the Numerical Rating Scale, Neck Disability Index, Quick Disabilities of the Arm, Shoulder, and Hand, Cervical Radiculopathy Impact Scale, and a 4-question neuropathic pain questionnaire were completed. Cronbach’s alpha (α) and ICC tests assessed reliability. Confirmatory factor and Spearman correlation analyses assessed validity. Results: Internal (α = 0.921) and test-retest reliability (ICC > 0.9, P < .001) were high across total and subscales (continuous, intermittent, neuropathic, emotional). TR-SF-MPQ-2 scores correlated with other scales (r = 0.404–0.648, P < .001). Confirmatory factor analysis supported a four-factor structure. Conclusion: TR-SF-MPQ-2 is valid and reliable for Turkish CRRP patients.